Cost implication of Line Voltage variation on Three Phase Induction Motor operation - Aderibigbe Israel Adekitan; Bukola Adetokun; Tobi Shomefun; Alex Aligbe (Universitas Ahmad Dahlan, 2018)
Globally, there is a drive toward ensuring energy efficiency in all aspect of production operations and power supply systems. Industries are the backbone of our modern word, and a significant percentage of industrial operations are motor driven. Three Phase Induction Motor is massively deployed in industries due to its ruggedness, reasonable cost and ease of maintenance. The energy efficiency of the induction motor is affected by the internal configurations of the motor and the nature of the supply. Power supply fluctuations result in power quality issues and its attendant negative effects on equipment operation. This research, studies the cost and performance implication of the effects of balanced over voltage, balanced voltage, balanced under voltage and unbalance voltage on the operation of the three phase induction motor using the peculiarities of Nigeria. The result shows that, there is an increase in operational cost due to increased energy loss in the windings as a result of voltage variations from the balanced state, with balanced over voltage operation showing more cost severity among the voltage variations considered.